PERMUKIMAN DI SEPANJANG DAERAH ALIRAN SUNGAI BIANG KEKE DAN CALENDU KABUPATEN BANTAENG, SULAWESI SELATAN - nfn Hasanuddin (WalennaE, 2009)
Bantaeng is one of the regencies in South Sulawesi which has history that came since 13th century. There are many cultural remains found in this area especially from prehistoric and Islamic period. Bantaeng was still a small kingdom in southern Sulawesi peninsula. The whole site has been surveyed along the Biang Keke River at the east side of Bantaeng and the Calendu River in the middle side of Bantaeng. The presence of big rivers with its branch that get upstream at Lompobattang's mountainside and flows across many Bantaeng's regions, allows the creation of settlement that rely on the farm fecundity and availability of fresh water. In later times, the settlements along the river flows of Biang Keke and Celendu river is constitute a small kingdom that depends on trade and agriculture sector.Bantaeng adalah salah satu kabupaten di Sulawesi Selatan yang memiliki sejarah sejak abad ke-13. Ada banyak sisa-sisa budaya yang ditemukan di daerah ini terutama dari periode prasejarah dan Islam. Bantaeng masih merupakan kerajaan kecil di semenanjung Sulawesi selatan. Seluruh situs telah disurvei di sepanjang Sungai Biang Keke di sisi timur Bantaeng dan Sungai Calendu di sisi tengah Bantaeng. Kehadiran sungai-sungai besar dengan cabangnya yang berhulu di lereng gunung Lompobattang dan mengalir melintasi banyak wilayah Bantaeng, memungkinkan terbentuknya permukiman yang mengandalkan kesuburan pertanian dan ketersediaan air tawar. Di kemudian hari, pemukiman di sepanjang aliran sungai Biang Keke dan sungai Celendu merupakan kerajaan kecil yang tergantung pada sektor perdagangan dan pertanian.